Relationship between the Biofilm-Forming Capacity and Antimicrobial Resistance in Clinical Acinetobacter baumannii Isolates: Results from a Laboratory-Based In Vitro Study - Matthew Gavino Donadu (MDPI AG, 2021)
The relationship between the multidrug-resistant (MDR) phenotype and biofilm-forming capacity has been a topic of extensive interest among biomedical scientists, as these two factors may have significant influence on the outcomes of infections. The aim of the present study was to establish a possible relationship between biofilm-forming capacity and the antibiotic-resistant phenotype in clinical Acinetobacter baumannii (A. baumannii) isolates. A total of n = 309 isolates were included in this study. Antimicrobial susceptibility testing and the phenotypic detection of resistance determinants were carried out. The capacity of isolates to produce biofilms was assessed using a crystal violet microtiter-plate-based method. Resistance rates were highest for ciprofloxacin (71.19%; n = 220), levofloxacin (n = 68.61%; n = 212), and trimethoprim-sulfamethoxazole (n = 66.02%; n = 209); 42.72% (n = 132) of isolates were classified as MDR; 22.65% (n = 70) of tested isolates were positive in the modified Hodge-test; the overexpression of efflux pumps had significant effects on the susceptibilities of meropenem, gentamicin, and ciprofloxacin in 14.24% (n = 44), 6.05% (n = 19), and 27.51% (n = 85), respectively; 9.39% (n = 29), 12.29% (n = 38), 22.97% (n = 71), and 55.35% (n = 170) of isolates were non-biofilm-producing and weak, moderate, and strong biofilm producers, respectively. A numerical, but statistically not significant, difference was identified between the MDR and non-MDR isolates regarding their biofilm-forming capacity (MDR: 0.495 ± 0.309 vs. non-MDR: 0.545 ± 0.283; p = 0.072), and no association was seen between resistance to individual antibiotics and biofilm formation. Based on numerical trends, MER-resistant isolates were the strongest biofilm producers (p = 0.067). Our study emphasizes the need for additional experiments to assess the role biofilms have in the pathogenesis of A. baumannii infections.